Expediency heuristic in travel agency webpage - Soffia, Suliman (2011)
Travel agency webpage plays an important role nowadays. Day by day there is an increase demand on travel for any purpose and of any duration.Human computer interaction is commonly implemented in travel agency webpage.Previously,weak human computer interaction is implemented in the travel agency webpage, SMAS Travels Sdn Bhd.That is why planning a trip could be time consuming and confusing.In this project, strong human computer interaction will be implemented.This implementation will overcome the problem of time wasting and the customer can carry out their work productively. Therefore,strong implementation of human computer interaction is required to develop an efficient travel agency webpage.